Science Laboratory Environment and Attitude Towards Chemistry Lessons of Senior High School Students - John Mart Elesio (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study determined which domain of science laboratory environment best influenced the attitude towards chemistry lessons on senior high school Science, Technology, Engineering and Mathematics (STEM) students. The research design used in this study are non-experimental quantitative and descriptive-correlational technique, utilizing universal sampling procedure. The total respondents were 144 Grade 12 STEM students enrolled in a sectarian school of Davao City. Survey questionnaires on science laboratory environment and attitude towards chemistry lessons were used as the research instrument in data gathering. Utilizing the mean scores; science laboratory environment and attitude towards chemistry lessons among the respondents were both assessed at a high level. Moreover, obtained data revealed that there is a significant relationship between science laboratory environment and attitude towards chemistry lessons among senior high school STEM students. Furthermore, open-endedness and future intention to study science significantly influenced students’ attitude towards chemistry lessons, but its open-endedness best influenced among all the domains of science laboratory environment.